2020
DOI: 10.21203/rs.3.rs-35979/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MCL-1 plays an oncogenic role in breast cancer by modulating chemoresistance and stemness properties by activating Wnt/β-catenin

Abstract: Background Breast cancer is the most common malignant tumor and the leading cause of death in women. Chemotherapy is one of the most important treatments for breast cancer. However, the development of chemotherapy resistance is the main cause of 20–30% of breast cancer patients developing metastasis, leading to death. MCL-1, an anti-apoptotic protein, has not been found to contribute to chemotherapy resistance in breast cancer. Methods We used large gene panels to detect pathological sections of tumors in dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Moreover, MCL-1 expression can be considered a prognostic biomarker that may help assess the efficacy of chemotherapy (that is, response to chemotherapy) and its effect on inducing apoptosis. In fact, previous studies confirmed that overexpression of MCL-1 is closely associated with poor prognosis and poor outcome 45,62–64 . Interestingly, Lee et al showed that in a distinct immunohistochemical subtype of breast cancer patients, TNBC, resistance to chemotherapy develops as a consequence of the failure to induce a downregulation in MCL-1 expression 65 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, MCL-1 expression can be considered a prognostic biomarker that may help assess the efficacy of chemotherapy (that is, response to chemotherapy) and its effect on inducing apoptosis. In fact, previous studies confirmed that overexpression of MCL-1 is closely associated with poor prognosis and poor outcome 45,62–64 . Interestingly, Lee et al showed that in a distinct immunohistochemical subtype of breast cancer patients, TNBC, resistance to chemotherapy develops as a consequence of the failure to induce a downregulation in MCL-1 expression 65 .…”
Section: Discussionmentioning
confidence: 95%
“…In fact, previous studies confirmed that overexpression of MCL-1 is closely associated with poor prognosis and poor outcome. 45,[62][63][64] Interestingly, Lee et al showed that in a distinct immunohistochemical subtype of breast cancer patients, TNBC, resistance to chemotherapy develops as a consequence of the failure to induce a downregulation in MCL-1 expression. 65 In addition, Eustace et al reported that patients treated with lapatinib, an EGFR inhibitor, are more likely to have elevated MCL-1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The human stem cell hierarchy has a functional dependence on MCL1 for self-renewal capability [ 14 ]. Over-expression of MCL1 in breast cancer cells increased stemness features and resistance to chemotherapy while its inhibition had the opposite effect [ 31 ]. MALAT1 indirectly affects the expression of its downstream related genes through its interplay with mediators such as miRNAs [ 32 ].…”
Section: Discussionmentioning
confidence: 99%